Generalization of Banach Contraction Principle for Prešić’s Type Mappings in Soft Metric Spaces - Bijender Singh; Vizender Singh; Özlem Acar (Sahand Communications in Mathematical Analysis)
The objective of this paper is to highlight the idea of $k$-weakly and $2k$-weakly soft compatible mappings and their utilization in proving the main results. For this aim, we establish some fixed point results for the Prešić's type contractive mappings in the context of soft metric spaces, when the set of the parameter is finite. Also we give an example to show that the condition of finiteness on the set of parameter can't be omitted. Some examples are given to support main findings of this article. Finally, an application of a soft version of BCP in iterated soft function systems is established.